Pengaruh Brand Image Rokok Dunhill Terhadap Keputusan Pembelian Di Kota Pontianak - Edy Suryadi; Halimah A (Universitas Muhammadiyah Pontianak, 2015)
ssues raised in this study is about the effects of smoking Dunhill Brand Image Buying Decision Against In Pontianak. Forms of this study is deskriptif.Populasi in this study were all people who consume cigarettes Dunhill in Pontianak. The sample used in this study were 100 respondents by using a sampling technique in which the unknown population. Hasilregresi simple linear significant value of 0.197 is greater than 0.05 so it can be concluded that no significant regression coefficient and simple linear regression equation Y = 3.355 + 0,138X. The coefficient is positive that there is a positive influence between the brand image of Dunhill cigarettes with purchasing decisions in Pontianak. From the results of testing the feasibility of a model (Test F) the result is a simple linear regression model can not be used to predict the purchasingdecisions in Pontianak influenced by brand image of Dunhill cigarettes, as evidenced by the calculated F value is greater than the significant level of confidence 0.05, then the model simple linear regression can not be used to predict pembelian.Sedangkan decision to test the correlation (r) has the effect of very low, with the correlation of 0.130 and for the test of determination (R2) has the effect of 17%. Purchase decisions in Pontianak influenced by brand image of Dunhill cigarettes, while the rest influenced by other variables.